STRATEGI PENGEMBANGAN TENUN RANGRANG SEBAGAI PRODUK WISATA ANDALAN NUSA PENIDA BALI - Firlie Lanovia Amir; I Gusti Made Riko Hendrajana (Institut Pariwisata dan Bisnis Internasional, 2018)
This study was made to study the potential of Tenun Rangrang of Nusa Penida, as well as to determine strategies and programs that can be done to develop the potential of Tenun Rangrang as tourism product. This study uses a qualitative descriptive approach to measure related variables, and uses SWOT matrix to explain and determine data in the formulation of strategies and programs. From the results of data processing, there are several decisive factors in the development of the potential of Tenun Rangrang, which are incorporated in internal and external factors. Of the two factors has successfully formulated 4 strategies and programs to develop them, including the SO strategy (developing the appeal of Tenun Rangrang including the surrounding environment), ST (Developing cultural tourism in Nusa Penida), WO (doing the right promotion), and WT (related to human resource development). It is hoped that this research can also be a reference for several policies that can be taken by the local government to develop tourism in Nusa Penida, as well as for people to be able to develop the potential of Tenun Rangrang to be much better.Â Keywords: Potential, Tenun Rangrang, Sustainable Tourism